Kebutuhan Seksual Menjadi Penyebab Utama Tingginya Angka Perceraian - Alfina Wildatul Fitriyah (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2021)
Sexual needs are one of the factors that often cause rifts in the household, the harmony that should be created is lost little by little because the needs of mental sustenance are not met. This can have a negative impact on the sustainability of the household so that it does not cause a little divorce. To minimize the number of divorce rates, the sexual needs of couples must be considered again. This research uses the field research method, which is research carried out directly into the field to ask and observe the people who are being researched through interactions to learn about them, their life history, their habits, their hopes, fears, and dreams. Researchers meet new people or communities, develop friendships, and discover new social worlds, often considered fun. The results of research on divorce problems caused by factors of sexual need are caused by the lack of good communication between husband and wife in conveying the desire of sexual desire that makes husband and wife no longer able to maintain their domestic relationship. According to Islamic law, sexual relations are one of the obligations of the husband and become the right of isti in his mental sustenance.